2014
DOI: 10.3168/jds.2014-8057
|View full text |Cite
|
Sign up to set email alerts
|

The role of sodium in the salty taste of permeate

Abstract: Many food companies are trying to limit the amount of sodium in their products. Permeate, the liquid remaining after whey or milk is ultrafiltered, has been suggested as a salt substitute. The objective of this study was to determine the sensory and compositional properties of permeates and to determine if elements other than sodium contribute to the salty taste of permeate. Eighteen whey (n=14) and reduced-lactose (n=4) permeates were obtained in duplicate from commercial facilities. Proximate analyses, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 58 publications
6
37
0
2
Order By: Relevance
“…Variability was also observed among permeates from different suppliers (3.9-95%). However, total nitrogen and selected mineral analysis of potassium, calcium, magnesium, sodium, and chloride for all 5 permeates were not different (P > 0.05), which suggests that the differences in hydrolysis were due to other component differences (Frankowski et al, 2014) or to differences in other minerals such as zinc, phosphate, or manganese (Kim et al, 1997; results not shown). Fresh liquid permeate had similar results to milks, where LL resulted in the lowest hydrolysis (>86%) compared with the other 3 enzymes (>96%; P < 0.05).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Variability was also observed among permeates from different suppliers (3.9-95%). However, total nitrogen and selected mineral analysis of potassium, calcium, magnesium, sodium, and chloride for all 5 permeates were not different (P > 0.05), which suggests that the differences in hydrolysis were due to other component differences (Frankowski et al, 2014) or to differences in other minerals such as zinc, phosphate, or manganese (Kim et al, 1997; results not shown). Fresh liquid permeate had similar results to milks, where LL resulted in the lowest hydrolysis (>86%) compared with the other 3 enzymes (>96%; P < 0.05).…”
mentioning
confidence: 59%
“…As such, we determined that hydrolyzed chocolate milk with permeate addition was not suitable for a consumer test. Frankowski et al (2014) reported that ingredients other than sodium, especially potassium and organic acids, in permeate contribute to salty taste. We detected no differences in aroma, cooked milk, or chocolate flavor of milks (P > 0.05).…”
mentioning
confidence: 98%
“…On comparison of whey permeate with DLP, the latter was reported to have the greatest salt perception, as also reported by Frankowski et al . (). Soup formulations prepared with the addition of DLP, and other permeates, had highest overall liking and saltiness perception when compared with the control (i.e., no added salt) and facilitated a significantly lower sodium content of the soups.…”
Section: Future Applications Of Delactosed Permeatementioning
confidence: 97%
“…According to Frankowski et al . (), DLP contributes to salty taste due to its NaCl, potassium chloride (KCl), lactic acid, and orotic acid content, though the components that prominently contribute to the saltiness perception are lactic acid and KCl. The saltiness perception of DLP was reported to be higher than for regular whey permeate due to its higher content of minerals (Fig.…”
Section: Future Applications Of Delactosed Permeatementioning
confidence: 99%
See 1 more Smart Citation